The effect of leader-member exchange on job crafting in nursing: The mediating role of psychological safety - EMRE, İLKİM ECEM (My University, 2023)
BACKGROUND Nurses are expected to make prompt and accurate decisions, have high crisis management skills, and exhibit proactive behaviors due to the nature of their service. Nevertheless, this situation is thought to be affected by the directors\" approach and the working environment\"s structure. Therefore, this study aims to determine the mediating role of psychological safety in the effect of leader-member exchange on job crafting. METHODS This study is a descriptive cross-sectional study. The study was conducted with 782 nurses in Istanbul, Turkey. Structural equation modeling was used in the study. AMOS software was used for model analysis, and SPSS software was used for descriptive statistics and correlation analysis. RESULTS The results indicate that the effects of leader-member exchange on job crafting (β = .541, p < .05) and psychological safety (β = .430, p < .05) are statistically significant. Moreover, the effect of psychological safety on job crafting is statistically significant (β = .453, p < .05). Based on the path analysis, it was determined that psychological safety has a mediating role in the relationship between leader-member exchange and job crafting (Confidence Interval; LB=0.059, UB=0.172). CONCLUSION This study revealed that psychological safety is a mechanism that contributes to the explanation of the relationship between leader-member exchange and job crafting. The findings will create ideas for directors to provide a healthier working environment. This situation is predicted to bring more positive results for employees and patients.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Sosyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Sociology; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; HEALTH CARE SCIENCES & SERVICES; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Sağlık Politikaları; Halk, Çevre ve İş Sağlığı; Sağlık Bilgi Yönetimi; Health Policy; Public Health, Environmental and Occupational Health; Health Information Management; job crafting; leader-member exchange; nursing; psychological safety